2020
DOI: 10.1088/1741-4326/ab77e7
|View full text |Cite
|
Sign up to set email alerts
|

Fracture behavior of tungsten-based composites exposed to steady-state/transient hydrogen plasma

Abstract: Fracture behavior of tungsten-based composites exposed to steady-state/transient hydrogen plasma. Nuclear Fusion, 60(4), [046029].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…When the desired cross-section plane was approached within 100 μm, intermittent manual grinding steps and SEM analyses were applied to reach the desired plane with a few micrometers accuracy. Finally, the crosssection surface was polished with a 3 μm diamond suspension and finalized with electro-polishing [10]. By comparing the surface cracks near the indents before and after cross-section preparation, it was confirmed that no artifacts were introduced by the cross-section preparation.…”
Section: Post-mortem Characterizationmentioning
confidence: 93%
See 3 more Smart Citations
“…When the desired cross-section plane was approached within 100 μm, intermittent manual grinding steps and SEM analyses were applied to reach the desired plane with a few micrometers accuracy. Finally, the crosssection surface was polished with a 3 μm diamond suspension and finalized with electro-polishing [10]. By comparing the surface cracks near the indents before and after cross-section preparation, it was confirmed that no artifacts were introduced by the cross-section preparation.…”
Section: Post-mortem Characterizationmentioning
confidence: 93%
“…For the hydrogen plasma in Magnum-PSI, collective TS measurements revealed that the ion temperature is close to the electron temperature [36]. This conclusion was used to calculate the steady-state heat flux using the Bohm sheath theory [10]. Likewise, the ion impact energy to the surface on the center of the plasma beam was calculated to be ∼10 eV.…”
Section: In Situ Diagnosticsmentioning
confidence: 95%
See 2 more Smart Citations
“…5,6 These advantages are unfortunately coupled with very low fracture toughness characterized by brittle transgranular and intergranular failure regimes, which severely restrict the useful operating temperature window and create a range of fabrication difficulties. [7][8][9] Strategies such as different alloying elements (e.g. W-Cr, W-Re, W-Ta, W-Ti, W-V) or nanostructure engineered W are being investigated to improve the material processing and working properties to extreme irradiation environments.…”
Section: Introductionmentioning
confidence: 99%